Perception and valuation of geographical varieties of Chilean Spanish amongst Spanish-speaking subjects from Santiago de Chile - Rojas Gallardo, Dario (Boletín de Filología, 2012)
In this paper we describe the perception which Spanish-speaking subjects from Santiago de Chile have of the geographical variation of Chilean Spanish in terms of three dimensions: the similarity observed in the speech of various regions in relation to their own speech, the quality attached to regional varieties, and the pleasantness perceived in them. These perceptions reveal the attitudes that the subjects have towards the regional varieties of Chilean Spanish identified by themselves. We conclude that people from Santiago de Chile have a high degree of linguistic self-esteem as they show a more favourable attitude towards the variety of Spanish spoken in the capital city and in the central region of Chile, in general, than towards the varieties spoken in the northern and southern regions. Nevertheless, in the affective dimension (pleasantness) and specially amongst people from the middle and lower classes, the southern variety increases its positive valuation, although never surpassing the positive valuation of the central region of this country.